Coup D'état in Honduras, 2009: A Case for the Study of International Mediation - Sáenz Leandro, Ronald (2019)
The paper seeks to examine the international mediation process carried out by the former president of Costa Rica, Óscar Arias Sánchez, as a result of what happened in the days after the coup d'état in Honduras, perpetuated on June 28 of the year 2009. Its objective is to analyze the characteristics of the conflict and frame its management intent as a case study for international mediation in peace contexts, helping to discern its characteristics and reviewing the role of the mediator within these situations. Concludes that international mediation stands as an area of study little developed by the theory of alternative dispute resolution (ADR) applied in Political Science, calling for rethinking its role for the promotion of alternative values of democratic dialogue.